Wireless LAN security (IEEE 802.11b) - Mohammad, Iftheker; Elahi, Mohammad Ashik (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.